Exploring imaged capillary isoelectric focusing parameters for enhanced charge variants quality control - Ghizzani, Virginia; Ascione, Alessandro; Gonnella, Federico; Massolini, Gabriella; Luciani, Francesca (Frontiers in Chemistry, 2025)
Biopharmaceuticals are increasingly utilised in the treatment of oncological, inflammatory, and autoimmune diseases, largely due to their exceptional specificity in targeting antigens. However, their structural complexity, heterogeneity, and sensitivity pose crucial challenges in their production, purification, and delivery. Charge heterogeneity analysis, a Critical Quality Attribute of these biomolecules used in their Quality Control, is often performed using separative analytical techniques such as imaged capillary Isoelectric Focusing (icIEF). Recognized as a gold standard by the industry, icIEF leverages a pH gradient to provide high-resolution profiling of charge variants in biotherapeutics. In this review, critical experimental parameters for icIEF method development in the context of biotherapeutic drug development and QC will be discussed. Key aspects, including sample preparation, capillary properties, carrier ampholytes, stabilizers, and detection are examined, and supported by recent literature. Advances in icIEF technology and its expanding applications underline its robustness, reproducibility, and compliance with regulatory standards, affirming its pivotal role in ensuring the identity and consistency of biological products.